2015
DOI: 10.1093/icvts/ivv080
|View full text |Cite
|
Sign up to set email alerts
|

Development of an algorithm to plan and simulate a new interventional procedure

Abstract: Here we have developed a new technically feasible algorithm simulating important aspects of a novel interventional procedure prior to the actual procedure. This algorithm can be applied to virtually all patients requiring a novel interventional procedure to help identify risks and find optimal parameters for prosthesis selection and placement in order to maximize safety for the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A combination of multi-slice CT (MSCT) and 3D TEE produces a more ideal model compared with MSCT alone [33,34]. Fujita et al [35] developed a preoperative algorithm encompassing chest X-ray, echocardiography and 3D printing for the preoperative evaluation of congenital heart diseases. Although the algorithm minimizes potential misunderstandings of cardiac anomalies, it also brings unnecessary imaging examinations and additional costs.…”
Section: Can a Static Cardiac Model Represent A Real Dynamic Heart?mentioning
confidence: 99%
“…A combination of multi-slice CT (MSCT) and 3D TEE produces a more ideal model compared with MSCT alone [33,34]. Fujita et al [35] developed a preoperative algorithm encompassing chest X-ray, echocardiography and 3D printing for the preoperative evaluation of congenital heart diseases. Although the algorithm minimizes potential misunderstandings of cardiac anomalies, it also brings unnecessary imaging examinations and additional costs.…”
Section: Can a Static Cardiac Model Represent A Real Dynamic Heart?mentioning
confidence: 99%
“…Furthermore, in the transcatheter implantation era, the choice of a sutureless device with a larger EOA ensures a great Valve-in-Valve feasability. (14) A limitation to our analysis consists of the use of projected EOAs values provided by the manufacturers. As a matter of fact, in the immediate intraoperative/ postoperative period, considering the hemodynamic variability due to the surgical catecholamine stress and volume load, the use of the continuity equation as a reliable method to estimate the EOA is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to objectivity and reproducibility, selection of cardiac phase is crucial for the assessment and production of 3D printed models [8,25]. Recent studies reported the advanced feasibility of 3D printed models for TAVI procedures, such as ex vivo studies of valve-in-valve procedures [26].…”
Section: Cardiac Valvesmentioning
confidence: 99%
“…SHDs refer to 'non-coronary cardiovascular disease' that can be treated by trans-catheter interventions; they range from pediatric and adult CHD to acquired heart valvular disease [8,9,[19][20][21][22][23][24][25][26][27][28][29][30][31] and other cardiovascular diseases. For less-invasive non-openheart interventions, precise 3D anatomy is crucial for from diagnosis, to procedural planning and simulation of trans-catheter intervention (Fig.…”
Section: Structural Heart Diseasesmentioning
confidence: 99%